2023
DOI: 10.3390/ijms24065125
|View full text |Cite
|
Sign up to set email alerts
|

NETs Promote Inflammatory Injury by Activating cGAS-STING Pathway in Acute Lung Injury

Abstract: Acute respiratory distress syndrome (ARDS) threatens the survival of critically ill patients, the mechanisms of which are still unclear. Neutrophil extracellular traps (NETs) released by activated neutrophils play a critical role in inflammatory injury. We investigated the role of NETs and the underlying mechanism involved in acute lung injury (ALI). We found a higher expression of NETs and cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) in the airways, which was reduced by Deoxyribonucleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…This reduction in neutrophil infiltration may be attributed to the suppression of the cGAS‐STING pathway, a DNA‐sensing pathway that regulates the expression of inflammatory chemokines and cytokines. [ 30 ] A recent study has also demonstrated that the inhibition of the cGAS‐STING pathway reduces neutrophil infiltration in the ALI mouse model. [ 31 ] These results demonstrate that pharmacological inhibition of NETs by DCNV can attenuate the inflammatory response in the ALI mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in neutrophil infiltration may be attributed to the suppression of the cGAS‐STING pathway, a DNA‐sensing pathway that regulates the expression of inflammatory chemokines and cytokines. [ 30 ] A recent study has also demonstrated that the inhibition of the cGAS‐STING pathway reduces neutrophil infiltration in the ALI mouse model. [ 31 ] These results demonstrate that pharmacological inhibition of NETs by DCNV can attenuate the inflammatory response in the ALI mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary ALI was induced by intratracheal injection of Lipopolysaccharide (LPS) (10 mg/kg, from Pseudomonas aeruginosa 27316, Sigma-Aldrich, USA, L9143) dissolved in 50 μl sterile PBS. Additionally, we used intraperitoneal injection of LPS (25 mg/kg) to construct sepsis-related ARDS, known as extra-pulmonary ALI ( 18 ). The mice enjoyed free access to food and water and were monitored until sacrificed 24 h after the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophils are one of the most common effector cells of the innate immune system and play an instrumental role in cardiovascular pathophysiology, in addition to their anti-infective function [ 134 , 135 ]. Neutrophil extracellular traps (NETs) released by activated neutrophils play a crucial role in inflammatory injury [ 136 ]. Numerous recent studies have shown that NETs are associated with CVDs, such as AS [ 137 ], myocarditis [ 138 ], and MI [ 139 ], which may be related to the unique cell death program of neutrophils called "NETosis,” “NETosis” releases granules, cytoplasmic guanosine-conjugated chromatin, and bactericidal proteins to form a reticulum during cell death that plays a crucial role in host defense, autoimmunity, and blood coagulation [ 140 ].…”
Section: Future Expectationsmentioning
confidence: 99%